Author Correction: Salt concentration and charging velocity determine ion charge storage mechanism in nanoporous supercapacitors - C. Prehal (Nature Portfolio, 2019)
The original version of this Article contained an error in the Acknowledgements, which incorrectly omitted from the end the following: ‘The research leading to these results has received funding from the European Community’s Horizon 2020 Framework Programme under grant agreement nº 730872.’ This has been corrected in both the PDF and HTML versions of the Article.